Women empowerment through functional literature education based on entrepreneurship - Rimayasi Rimayasi; L.M. Azhar Sa'ban; Andy Arya Maulana Wijaya (Universitas Muhammadiyah Magelang, 2022)
Women are expected to be empowered more quickly and effectively through entrepreneurship-based functional literacy education. The main problem faced is that women drop out of school quite high and do not have skills. This Community Service Activity (PKM) collaborates with the Bungaeja Community Learning Activity Center in an entrepreneurship-based functional literacy education program. The community empowerment method used consists of counseling and training. From community service activities, it can be concluded that HR is not enough to only master theories, but also requires skills in applying their knowledge in society. In training and mentoring, partners can make handicraft products from plastic waste.